2=2(k+3)+4(5-2k)

Simple and best practice solution for 2=2(k+3)+4(5-2k) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2=2(k+3)+4(5-2k) equation:


Simplifying
2 = 2(k + 3) + 4(5 + -2k)

Reorder the terms:
2 = 2(3 + k) + 4(5 + -2k)
2 = (3 * 2 + k * 2) + 4(5 + -2k)
2 = (6 + 2k) + 4(5 + -2k)
2 = 6 + 2k + (5 * 4 + -2k * 4)
2 = 6 + 2k + (20 + -8k)

Reorder the terms:
2 = 6 + 20 + 2k + -8k

Combine like terms: 6 + 20 = 26
2 = 26 + 2k + -8k

Combine like terms: 2k + -8k = -6k
2 = 26 + -6k

Solving
2 = 26 + -6k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '6k' to each side of the equation.
2 + 6k = 26 + -6k + 6k

Combine like terms: -6k + 6k = 0
2 + 6k = 26 + 0
2 + 6k = 26

Add '-2' to each side of the equation.
2 + -2 + 6k = 26 + -2

Combine like terms: 2 + -2 = 0
0 + 6k = 26 + -2
6k = 26 + -2

Combine like terms: 26 + -2 = 24
6k = 24

Divide each side by '6'.
k = 4

Simplifying
k = 4

See similar equations:

| (6+2i)(-4-3i)= | | 5x+4=10-x | | -20=-4a-6a | | 3/4(24-8b)=3(5b+1) | | (3x+2)-(2x-3)=-10 | | -4(4a-2)=88 | | 4-2(v-7)=-8 | | 4-4v=-(v+2) | | 17-x=23 | | 6(6b+2)=192 | | 6(y-3)=3y-30 | | (x+5)(x^2+10x+25)=0 | | 4(920-x)+2x=2446 | | 8z=12-28 | | 2x+36=4x | | 5(d+1)-4d=51-5d | | -6(-6r+3)-6=120 | | 2(6-10m)=10(2m-6) | | x+4+8x=4 | | 8+x=2x | | 23x+43-31+45=3254 | | 6x+9=x-8 | | 5(-6-4n)=-110 | | 4k^2-81=0 | | 2(-10m)=10(2m-6) | | 5r+7R+6R-6= | | 5x^2-33x+40=0 | | 23x+43-31+45=264 | | 2x+6(-4-3x)=72 | | -3(h+1.4)=(5-h)11 | | 5x+5-1.8=14.7 | | 11x+1=x-13 |

Equations solver categories